Comparaison internationale de l’utilisation de la main-d’oeuvre dans l’industrie : un programme linéaire - Parker, Ruth (L'Actualité économique, 1974)
AbstractThis linear programming model for educational planning, by allowing for choice among techniques of production, permits the introduction of non-constant factor substitution into the production function. The model is applied to educational planning in France and treats simultaneously four kinds of educated manpower and capital in the seven major industrial sectors of an economy. Alternative techniques are drawn from seven other countries for which reasonably comparable data are available. These techniques of production define the production function and determine the demand for educated manpower and capital independently of the supply of these factors.An initial static model maximizes GNP (holding its composition constant) subject to a fixed supply of manpower and capital. The model thus tests whether supply is the constraining factor in the choice of technique in theshort run. In the case tested, it is.In the dynamic version of the model, supply is allowed to increase by means of education (for manpower) and investment (for physical capital). Consumable GNP, that is GNP net of the cost of education and investment, is maximized. Terminal capital stock problems make it impossible to test the model directly. The problem is then broken down into two steps: the identification of the techniques (one for each industry) which permit the greatest net contribution to GNP, and the movement in time towards these "optimal" techniques. The first of these steps is solved using a dual version of the model, but the second is not attempted in this paper.